Current directions in searching for tuberculostatic substances - Żwawiak, Justyna; Zaprutko, Lucjusz (Journal of Medical Science, 2014)
Yearly, 8 milion people advance to active tuberculosis (TB) and nearly 2 milion victims die of their infection. Long drug regimen is blamed for the emergence of drug resistant TB. Moreover, 20% of TB isolates are already resistant to the first line antituberculosis drugs. This situation has required to develop new, more active anti-TB substances. Several novel drug candidates from different groups of chemical compounds undergo clinical trials. Others, also promising agents, have been obtained recently. They are the basis for further modifications heading for improvement of their physicochemical, biological and toxicological parameters.